Super-resolution SERS Imaging of Single Particles in Cells - de Albuquerque, Carlos Diego L. (Anal Chem, 2020)
The ability to locate and identify molecular interactions in cells has significant importance for understanding protein function and molecular biology. Functionalized metallic nanoparticles have been used as probes for protein tracking and drug delivery due to their ability to carry therapeutic agents and readily functionalized surfaces. In this work, we present a super-resolution surface-enhanced Raman scattering (SERS) approach for imaging and tracking membrane receptors interacting with peptide functionalized gold nanostars (AuNS). The α(v)β(3) integrin receptors in colon cancer cells are successfully targeted and imaged using AuNS with the high affinity amino acid sequence arginine-glycine-aspartic acid-phenylalanine-cysteine (RGDFC) attached. The RGDFC peptide interaction with the integrin receptor provides a bright and fluctuating SERS signal that can be analyzed with localization microscopy algorithms. Additionally, the observed SERS spectrum is used to confirm protein-peptide interaction. Experiments with functionalized and bare AuNS illustrate specific and non-specific binding events. Specific binding is monitored with a localization precision of ~6 nm. The observed spatial resolution is associated with tight binding, which was confirmed by the slower diffusion coefficient measured from 4.4 × 10(−11) cm(2)/s for the AuNS-RGDFC compared to 7.8 × 10(−10) cm(2)/s for the bare AuNS. Super-resolution SERS images at different focal planes show evidence of internalized particles and suggest insights into protein orientation on the surface of cells. Our work demonstrates super-resolution SERS imaging to probe membrane receptor interactions in cells, providing chemical information and spatial resolution with potential for diverse applications in life science and biomedicine.